(3eLehYI CTYGQ aj Bd GdHjJs
(3ChdgG (B:s
(3jGCNj jGeDedj jGQLGFj jG cajdj, hCjf efj Gdcajd s
(3BNQgG (B:s
(3QeGfG GdOgoQ HGdNWH GdYHhS djJfj cfoJ aOGkA ddMSjf s
(3GdfSNI HgG MhGTs
(3Hjf SWhQgG HYV GdTQhM hGdeYGfjs
(3hHgG fXGe GdJYbjHIs
(3deLehYI ef GdTYQGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdCOHs